Uma análise funcionalista da modalidade epistêmica e da evidencialidade em discursos políticos - Alves, Rosangela Jovino (2010)
The study of modalities is complex and involves various aspects of language in use, because speakers modalize their speech according to their needs and to the communicative context in which he is inserted. This paper analyzes epistemic modality, which is related to the knowledge of the speaker and the consideration of that knowledge in the form of certainty, doubt or compromise. It also investigates evidentiality, category responsible for representing the sources that the speaker has to give security to the information provided in his speech, and that allows the speaker to insert himself as a source or specify a source responsible for the information. The corpus is formed by speeches by Senator Marina Silva and Senator Heloisa Helena, due to the reference that they have in Brazilian politics, and to the fact that their speeches are often target of polemics and always have a strong impact on the society. The analysis of epistemic modality and evidentiality presents the ways and means of expression of these two discursive marks in the discourses of the senators. Thus, it is possible to identify how these two linguistic phenomena contribute to the formation of the ethos of the politicians, or how it contributes to the elaboration of the image that the speaker / subject of the discourse constructs to the listener identify and design in it. For coding of data concerning to the selected speeches, Systemic Coder program was used. This software enables quantitative analysis of frequency of occurrence of linguistic traces systemically. The analysis of the uses and modes of expression of epistemic modality and evidentiality revealed the salient features of political discourse, as the use of words expressing doubt, used by politicians to exempt a larger responsibility for the information. Subjectivity is also present in these speeches, allowing politicians to present their information based on their experiences of the world, allowing them to create a certain proximity to the listeners. The analysis of evidentiality also revealed that sources, especially those responsible for information presented as the most controversial or serious, are outsourced, freeing the speaker from responsibility for what is said, pointing to a qualified source, or even someone responsible for the information presented. This work, through the analysis of epistemic modality and evidentiality in political speeches, provides insights into the formation of the ethos of political figures, which has many of its features related to these linguistic traces.